Test Case Quality Factors (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The guarantee of software quality is very important. Thus, before a software is released to the end users, the flaws in the software should be detected by using high quality test cases. Currently, gauging the quality of test cases is carried out without any particular model and the criteria for good test cases is still unclear. Therefore, this study studies the literature using Systematic Literature Review (SLR) technique to identify the criteria of good test cases. The SLR considered papers between 2010 and 2018 in IEEE Xplore, ACM Digital Library, and Science Direct databases. Through the searching, it was found 310 papers are related. After filtering using exclusion and insertion criteria, 14 papers were considered for analysis. As a result, the test managed to identify 30 quality factors from the selected articles. These quality factors were additionally inspected, arranged and finished to be incorporated as the quality factors of test cases evaluation metrics.